2020
DOI: 10.3390/app10030738
|View full text |Cite
|
Sign up to set email alerts
|

Immunochromatographic System for Serodiagnostics of Cattle Brucellosis Using Gold Nanoparticles and Signal Amplification with Quantum Dots

Abstract: In this article, we describe an immunochromatographic test system developed for rapid serodiagnostics of cattle brucellosis using two markers: Gold nanoparticles (GNPs) and quantum dots (QDs). The test system was compared with immunochromatographic serodiagnostics systems that use only one marker. The approbation of the test system was conducted on samples of cattle sera with low, but diagnostically significant titers of specific antibodies. We show that when two conjugates are used, the intensity of the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The serum samples of cows were collected in the course of previous investigations of the authors [23][24][25]27]. Blood serum were obtained from the "Russian Black Pied" and 'Red Steppe' cattle breeds aged from 1 to 4 years and weighing from 200 to 450 kg, "Kazakh Whiteheaded" cattle breed mostly at the age of 2 years and weighing from 200 to 550 kg.…”
Section: Serum Panelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum samples of cows were collected in the course of previous investigations of the authors [23][24][25]27]. Blood serum were obtained from the "Russian Black Pied" and 'Red Steppe' cattle breeds aged from 1 to 4 years and weighing from 200 to 450 kg, "Kazakh Whiteheaded" cattle breed mostly at the age of 2 years and weighing from 200 to 550 kg.…”
Section: Serum Panelsmentioning
confidence: 99%
“…Immunochromatographic tests for serodiagnosis of brucellosis in animal species have been described [22][23][24][25]. Kim et al have developed an immunochromatographic system for the detection of specific antibodies against the bovine leukemia virus [26].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, studies indicated that ferrite NPs are used as a diagnostic tool for high saturation magnetization, tissue relaxivity, clarity, and exact localization of these particles in the target tissue [9][10][11][12]. It is reported that iron oxide being ferrite in nature is extensively used in various fields of nanotechnology [13][14][15]. Reports indicate that among different ferrites, nickel and cobalt ferrites are also used to increase the high magnetic moment of ferrites in biomedical applications [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The disease is an ancient disease that has been known under various names, including gastric remittent fever, Mediterranean fever, undulant fever, Malta fever, Bang's disease, and Rock fever of Gibraltar. Humans are accidental hosts; but brucellosis remains a major public health issue across the globe and is the most common zoonosis (Diab et al 2018;Sotnikov et al 2019).…”
Section: Introductionmentioning
confidence: 99%